Mathematical modelling of rare earth elements recovery by ion exchange leaching from ion adsorption clays - Nurul Aniyyah, Mohamad Sobri (2024)
Ion adsorption clays are identified as a promising source to meet the growing demand for rare earth elements (REEs). Current research trends aim to enhance REE leaching efficiency through experimental investigations to identify the most effective leaching solutions and optimum leaching conditions. Despite intense investigations of REEs recovery using ion exchange leaching, the theory of the cation exchange mechanism involved has not been completely understood. Considering the complexity of the leaching process and the limitations of experimental works that are costly and time-consuming, modelling and simulation methods present a promising approach. Therefore, the objectives of this study are to determine the thermodynamic stability of REE ions using different types of leaching solutions under various leaching conditions and to formulate a mathematical model representing the ion exchange leaching process using the Shrinking Core Model. A thermodynamic stability study was conducted using HSC Chemistry 10.0 software through Pourbaix diagrams analysis. The thermodynamic stability of REE species of La, Nd, and Y was evaluated in the three different types of leaching solutions of ammonium sulfate ((NH4)3SO4), magnesium sulfate (MgSO4), and aluminum sulfate (Al2(SO4)3) under various leaching solution concentration (0.05-0.6 M) and leaching temperature (25–80 °C). The Pourbaix diagrams analysis demonstrated that the MgSO4 solution was the most effective leaching solution in achieving the maximum thermodynamic stability region of La3+, Nd3+, and Y3+ across all concentrations from 0.05 to 0.6 M without any chemical formation within that region, at 25 °C within a pH range of 0 to 5.8. Maintaining a temperature of 25°C is recommended in this study as higher leaching temperatures were found to decrease the thermodynamic stability region of La3+, Nd3+, and Y3+. This indicates that ion-exchange leaching can be efficiently carried out at room temperature, eliminating the requirement for external heating. Based on the Shrinking Core Model, a kinetic model was successfully formulated based on the ratedetermining step equation which belonged to the internal diffusion control. The values of the rate constant and reaction order were determined by using the experimental data of REE leaching efficiency versus leaching time at different concentrations of MgSO4 solution (0.05-0.4 M). The calculated value was 0.005, and the initial value of 1.53 was later modified to 1.33 due to a deviation exceeding 10% in the NRMSE value. The statistical model validation demonstrated a high level of agreement with the index values of = 0.978, indicating an excellent agreement of simulation data with experimental data, and a low value of NRMSE = 7.9 %, indicating an excellent performance model. The model consistently exhibits exponential growth in REE leaching efficiency, eventually reaching a maximum of 100% as leaching time progresses, demonstrating the leaching behaviour of REE extraction observed in this model follow the patterns observed in the leaching experiment. In conclusion, MgSO4 was identified as the most effective leaching solution and 25 °C as the best leaching temperature for achieving the maximum thermodynamic stability region for La, Nd, and Y. Additionally, the developed kinetic model has the potential to provide reliable data on REE leaching efficiency at different leaching times across various concentrations of MgSO4 solution, benefiting industry stakeholders, government agencies, and policymakers and advancing the progress of REE extraction from ion adsorption clay in Malaysia